DESKRIPSI FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENUNDAAN WAKTU EKSTUBASI POST GENERAL ANESTESI DI RSUP PROF. DR. R.D KANDOU MANADO - Meifi Pamela Koraag; Adriatna Sekar Siwi; Pramesti Dewi (Jurnal Cakrawala Ilmiah, 2022)
Extubation is the process of removing a tube from the upper respiratory tract. Often clinicians have difficulty in determining the right time to extubate. Extubation that is too fast (premature) will cause extubation failure so that the patient requires reintubation. This study aims to describe the factors associated with the delay of anesthesia extubation in post general time in RSUP. Prof.dr. R.D. Kandou Manado. This type of research is descriptive research. The sample used in this study were patients who experienced delayed post general anesthesia extubation at the Central Surgical Installation of RSUP Prof. dr. R.D Kandou Manado using the Slovin formula obtained as many as 81 samples. The sampling technique used is simple random sampling. Data were analyzed univariately to determine the frequency and percentage of factors to be described, namely Age, Gender, GCS (Glascow coma scale), systolic blood pressure, duration of surgery, type of surgery and Tidal volume of patients who experienced delayed extubation. Of the 81 samples that experienced post-general anesthesia extubation delays, it was found that for the age factor 56 (69.1%), female sex 43 people (53.1%), GCS Glascow coma scale) 46 people (56.8%), systolic blood pressure <90 mmHg 49 people (60.5%), patients who underwent long surgery 67 people (82.7%), patients with severe type of surgery 38 people (46.9%), and Patients with tidal volume <300 44 people (54.3%).